Scaling functional diversity of small mammals in desert systems - Rodriguez, Maria Daniela (2014)
Although scaling biodiversity is a common topic in ecology, scaling functional biodiversity is a major theoretical and analytical challenge, mainly because trait differentiation and regulating processes occur at different spatial scales. Here we propose a method to scale functional biodiversity by comparing the relative dominance of convergent vs. divergent functional traits across environmental gradients. Particularly, in highly variable systems such as deserts one would expect species convergence in the use of an abundant resource through niche filtering, promoting functional redundancy (stability hypothesis), but at which spatial scale? We tested this approach using small mammal assemblages of the Monte desert (Argentina, South America) and found that divergent traits are dominant on smaller spatial scales while convergent traits are present only at the highest spatial scale. Functional complementarity was recorded at the community and meta?community levels, suggesting that niche partitioning is the main regulating process and diet the major divergent trait. At regional scale, divergent traits were present indicating that biodiversity is also regulated by niche filtering. Finally, we found that the stability hypothesis cannot be generalized for desert systems but depends on the spatial scale. This novel approach offers new insights into the search for an integrative perspective on functional biodiversity.